2000
DOI: 10.1001/jama.284.4.472
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in the Treatment of HIV Lipodystrophy Syndrome

Abstract: This study suggests that a relatively low dosage of metformin reduces insulin resistance and related cardiovascular risk parameters in HIV-infected patients with lipodystrophy. JAMA. 2000;284:472-477

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
2
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 334 publications
(178 citation statements)
references
References 25 publications
5
164
2
7
Order By: Relevance
“…in HIV-infected patients modeled after the DPP, do suggest reductions in HbA1c over 6 months (60). Insulin sensitizing agents may be useful to reduce insulin resistance and may also help to reduce central fat accumulation (67) or even to increase peripheral fat in some lipoatrophic insulin resistant patients (68), but should not be used for the sole purpose of improving body composition. Moreover, the risk profile of these drugs may be great, with the potential for interaction with ART.…”
Section: Prevention Strategies For Chd In Hiv-infected Patientsmentioning
confidence: 99%
“…in HIV-infected patients modeled after the DPP, do suggest reductions in HbA1c over 6 months (60). Insulin sensitizing agents may be useful to reduce insulin resistance and may also help to reduce central fat accumulation (67) or even to increase peripheral fat in some lipoatrophic insulin resistant patients (68), but should not be used for the sole purpose of improving body composition. Moreover, the risk profile of these drugs may be great, with the potential for interaction with ART.…”
Section: Prevention Strategies For Chd In Hiv-infected Patientsmentioning
confidence: 99%
“…Several studies have affirmed the value of metformin to slow or prevent progression of impaired glucose tolerance (IGT)/impaired fasting glucose (IFG) ('prediabetes') to type 2 diabetes and other studies have suggested a place for metformin in the [84][85][86][87]. Reduced cancer risk was tentatively indicated in the UKPDS and has subsequently been identified in large database analyses, suggesting that metformin might protect against certain cancers in individuals with type 2 diabetes, notably in the bowel where drug exposure is high, and this has opened a whole new research arena [69,88,89].…”
Section: Other Indicationsmentioning
confidence: 99%
“…42 Hadigan et al demonstrated a 6-fold increase risk of impaired glucose tolerance among HIV-infected patients with clinical and subjective evidence of fat redistribution compared to age and BMI-matched subjects from the Framingham Offspring Cohort (30 vs 5%). Subjects with abnormal fat redistribution also had an increased prevalence of diabetes mellitus (8% vs. 0.5%) compared to the Framingham subjects 43 . The insulin resistance demonstrated in HIV patients is considered by most authors to confer a high risk of coronary artery disease (CAD) in these subjects.…”
Section: Metabolic Disorders Pancreatic Dysfunction and Glucose Metabmentioning
confidence: 90%